Evaluating the coordination of motor abilities in Greco-Roman wrestlers by computer testing - Gierczuk, D.; Ljach, W. (Human Movement, 2012)
Purpose. The aim of this study was to evaluate, by using a number of selected criteria, the accuracy of Vienna Test System (VST) computer tests used in wrestling to evaluate motor skill development. Methods. Fifteen 16-17-year-old students from the SMS Sports School in Radom, Poland, who had been practising Greco-Roman wrestling for a period of 3 to 6 years took part in a VTS-based examination that measured coordination of motor abilities (CMA). Test reliability and validity were evaluated on the basis of thirty test scores characterising six abilities that define motor coordination. Reliability was defined by performing the tests twice (test/retest) over a period of three-to-five days. The validity of the selected scores was established with the help of three different criteria. Results. Thirteen out of the thirty CMA scores under investigation demonstrated sufficient coefficients of reliability. The CMA tests assessing quick reaction time, frequency of movements, partial spatial orientation, movement adaptability and movement coupling fulfilled the assumed criterion. In most cases, the coefficients of validity were not lower than 0.3. The highest validity level was demonstrated by scores measuring movement coupling, complex reaction time, spatial orientation and movement adaptability, while the lowest one was found in simple reactions and frequency of movements. Conclusions. The obtained reliability and validity coefficients of the scores based on complex reaction, partial spatial orientation, movement adaptability and movement coupling confirm the usefulness of these specific tests in diagnosing CMA in wrestlers, as they meet the demands of sports metrology.